Forum Theatre as a Health Promotion Intervention for Sensitive Issues of Sexual Violence and Reproductive Health: A Literature Review - Nur Afiaty Mursalim; Nur Indah Atifah Anwar; Irwandi Rachman (Global Health Practice Journal, 2026)
Background: Sexual violence and reproductive health issues remain major public health concerns among adolescents and young adults. Conventional health education often fails to address these sensitive topics effectively due to social stigma and limited participant engagement. Forum theatre has emerged as a participatory, arts-based approach that encourages dialogue, critical reflection, and active learning. Aim: This study aimed to analyze the effectiveness of forum theatre in improving knowledge, attitudes, self-efficacy, and behavioral intentions related to sexual violence prevention and reproductive health. Methods: A descriptive-analytical literature review was conducted using articles published between 2015 and 2024 from PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda. The selection process followed PRISMA guidelines. A total of 12 studies met the inclusion criteria and were analyzed using thematic synthesis. Results: Forum theatre interventions consistently improved participants’ knowledge of sexual consent and reproductive health (p<0.05), reduced acceptance of gender-based violence, and enhanced self-efficacy in resisting coercion and seeking help. Behavioral intentions, including reporting violence and practicing safer behaviors, also showed significant improvement. Emotional engagement and participatory learning were identified as key mechanisms driving these outcomes. Conclusions: Forum theatre is an effective and culturally adaptable approach for addressing sensitive issues in sexual violence prevention and reproductive health promotion. Its integration into educational and community-based programs may strengthen public health interventions.